Predicting Brand Loyalty by Brand Communities Instagram Users in Indonesia During the Covid-19 Pandemic - Heppy Meilysthia Putri; Tantri Yanuar Rahmat Syah (Penerbit Jurnal Indonesia, 2022)
Covid-19 pandemic has made changes in consumer behavior that dominate product purchases online rather than offline. This encourages every cosmetic company, especially face powder brands to continue to produce innovation and creativity in their Instagram content in order to provide a satisfying online shopping experience for teenage women in Indonesia. The purpose of this study was to determine the effect of online social media, social media brand communities, consumer brand promise & trust, consumer brand relationships, consumer brand engagement, customer satisfaction and brand loyalty on Instagram users in the face brand account community in Indonesia during the covid-19. This research was conducted on 120 respondents in Indonesia, Instagram users by collecting online questionnaire data conducted in August 2021. The research model, this study used SEM Lisrel. The results of data processing are obtained: online social media platforms have a positive effect on social media brand communities. Online social media platform has a positive effect on consumer brand promise & trust. Social media brand communities have a positive effect on consumer brand relationships. Social media brand communities have a positive effect on consumer brand engagement.